(untitled) (Journal of Atomic and Molecular Sciences, 2015)
A graphic method for studying multi-atom resonant photoemission process in molecules and solids is presented in this work. The Feynman diagrams have been applied to describe the interactions between atoms in MnO molecules. The theoretical results show that the resonant contribution exhibits a strong distance-independent and element specific effects for the neighboring atoms. Two mechanisms, the interactions between the atoms and the reabsorption process have been supposed in the present work to explain the multi-atomic resonant photoemission for the first time.